Analisis perancangan cooler box berbasis termoelektrik terhadap varian penggunaan thermal paste, faktor lingkungan dan heatsink - Imron Rosyadi; Haryadi Haryadi; Novreza Pratama; M Haikal Fasya; Ade Irman; Aswata Aswata; Yusvardi Yusuf (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
Thermoelectric is a semi-conductor module that is commonly used in portable cooler box because it is light, saves electricity and does not require a large space. This thermoelectric based on cooling technology design is expected to provide data and analysis results that help cooler box designers to produce the best performance The purpose of this research is to study the effect of using thermal paste, environmental factors and heatsink. The results of the study show that testing with thermal paste obtained the best conditions with the average temperature of the cold side being -1.17 oC with the best temperature being -6.05 oC. In the test conditions in the box if proven better than the open temperature conditions with a temperature difference of 7.4 oC. In the heatsink test, there was a decrease in performance caused by the influence of the conductivity of the heatsink material, which was 4.87o C.